Prevalence, correlates and characteristics of chronic pruritus: a population-based cross-sectional study - Matterne, Uwe; Apfelbacher, Christian J.; Loerbroks, Adrian; Schwarzer, Tamara; Büttner, Marion; Ofenloch, Robert; Diepgen, Thomas L.; Weisshaar, Elke (Acta dermato-venereologica, 2011)
Pruritus is the most frequent symptom in dermatology. Its impact on quality of life is substantial. Epidemiological data on chronic pruritus (> 6 weeks) at the population level is sparse, but is important in order to understand the burden and risk factors of this distressing symptom. The aim of this population-based cross-sectional study was to estimate the point, 12-month and lifetime prevalence of chronic pruritus, assessing its association with sociodemographic variables and describing its characteristics. A validated postal questionnaire was sent to 4,500 individuals in from the German General population. Three contact attempts were made. The response rate was 57.8% (n = 2,540). The point prevalence of chronic pruritus was 13.5% (95% confidence interval (95% CI) 12.2–14.9%), 12-month prevalence 16.4% (15.0–17.9%) and lifetime prevalence 22.0% (20.4–23.7%). Multivariate analyses found only ethnic origin independently associated with chronic pruritus. The impact of chronic pruritus on quality of life and emotional well-being appears to depend on severity rather than on the presence of the symptom alone. This is the first study to investigate various prevalence estimates of chronic pruritus at the population level. Despite its limitations (self-report and potential self-selection) this study indicates a high burden of chronic pruritus in society.